Performance of Domestically Made Surface Solar Radiation Observation System at Zhongshan Station, Antarctica - Zheng Xiangdong; Zhao Yong (应用气象学报)
Solar irradiance is one important element in conventional meteorology observations. Long-term observations of solar radiation by using China-made wide-band pyranometers have been carried out. However, the performance of instrumental systems is not sufficiently evaluated or analyzed, especially in the polar regions where harsh condition and large seasonal variations of solar elevation causes dramatic variation of surface solar irradiance. To fill this gap, the performance of the domestically made solar radiation observation systems at Zhongshan Station, Antarctica in 2017, including global solar radiation (GSR), direct solar radiation (DIR) and the diffuse solar radiation (DIF) measurements, is evaluated. The averaged nighttime thermal offsets of two domestic FS-6A pyranometers, respectively for GSR and DIF observations, are both less than 3 W·m-2, and their temporal variations are highly consistent. Compared with CM21 or CM22 pyranometer that reach the requirement of the second-class standard and are globally deployed, the additional heating effect of the auxiliary ventilation heater of FS-6A pyranometers significantly reduces the inherently physically-based correlation coefficient between the night thermal offset and the net longwave radiation, and the absolute values of FS-6A thermal offset significantly increase but are within 5 W·m-2 under higher wind speeds (noless than 15 m·s-1). The temporal variations of solar DIF irradiances from two FS-6A pyranometers are highly consistent under cloudy overcast condition, and their solar irradiance values are systemically lower (about -6 W·m-2 or -1%) than that of CM22 as the solar DIF irradiance is about 500 W·m-2 from CM22. However, the absolute (relative) difference is respectively lower than 2.6 W·m-2 (4.0%) as the solar zenith angle (θ) is less than 86 °. The GSR close examination suggests that the ratio of FS-6A GSR absolute difference from the sum of horizontally projected DIR and DIF meeting the requirement of threshold value (less than 2% or 15 W·m-2 with θ≤ 80°) proposed by the baseline surface radiation network (BSRN) is more than 80%. But only 44% samples meet the requirement of the BSRN threshold value (less than 3.5% or 20 W·m-2 with θ> 80°) when the four-quadrant tracking solar disk model is applied in operation. Under cloud-free condition, the measurements of GSR, DIR and DIF from the domestically made instruments are well comparable with the simulations from the parameterized solar radiation model that has been extensively applied in middle-low latitudes, and the correlation coefficients between the simulations and observations are more than 0.95. However, the observations are significantly higher than the simulations as the solar irradiance increases. The results suggest that China domestically made solar radiation observation system is fully qualified for the routine observation in polar regions.